Unconventional properties of engineered Au–Ag nanostructures. (1st August 2022) - Saha, Subham Kumar; Mondal, Pritha; Vasudeva, Navyashree; Mahadevu, Rekha; Thapa, Dev Kumar; Bhattacharyya, Biswajit; Sharma, Anand; Islam, Saurav; Mahapatra, Phanibhusan Singha; Phanindra Sai, T; Channagiri, Samartha A; Bellare, Pavithra; et al.
Abstract: Au–Ag nanostructures comprising of ∼1 nm Ag nanoparticles embedded into an Au matrix show several unconventional optical, electric and magnetic properties. Here, we review progress made towards the preparation of these materials as well as analysis of their structure. Further, electrical and magnetic transitions in these materials are discussed. Finally, we review the properties of these materials as revealed from optical and electron microscopic probes.